Professional contraction and the growth of teacher confidence. Experiences in the teaching of poetry from the Republic of Ireland and Northern Ireland. (4th May 2021) - Hennessy, Jennifer; Marlow, Nicola; Alexander, Joy; Dymoke, Sue
ABSTRACT: A rising crisis of confidence has been noted amongst teachers of poetry in recent years. Amplified by external factors such as high-stakes testing regimes, performance indicators, standardisation and accountability measures, teachers are increasingly challenged to provide immersive, imaginative and engaging encounters with poetry while developing and maintaining their sense of professional confidence. Drawing on data gleaned from 84 English teachers across the Republic of Ireland and Northern Ireland, this research explores teachers' sense of confidence in the teaching of post-16 poetry. The findings of this research indicate a strikingly high level of reported confidence amongst post-16 poetry teachers juxtaposed with low levels of informal poetry engagement, low levels of poetry-related in-service attendance and a reduced commitment to pedagogical innovation. The research points towards the emergence of a new professionalism in which teacher confidence is reinforced through professional contraction and compliance with practices of pedagogical standardisation.